2019
DOI: 10.1111/resp.13664
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high flow does not improve exercise tolerance in COPD patients recovering from acute exacerbation: A randomized crossover study

Abstract: Background and objective: We hypothesized that by reducing respiratory work and improving gas exchange, nasal high flow (NHF) would improve exercise tolerance in patients with chronic obstructive pulmonary disease (COPD) following respiratory exacerbation. Methods: This was a monocentric, randomized, controlled crossover study. Patients with severe to very severe COPD carried out two high-intensity constant work-rate exercise tests (CWRET) with and without NHF on two consecutive days. The primary outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…The authors reported that there were no improvements in endurance time or symptoms, such as dyspnea and leg discomfort, with HFNC utilization. 9 They did note, however, that transcutaneously measured partial pressure of carbon dioxide and heart rate during exercises were lower in the HFNC group than in the group receiving O 2 therapy. 9 The main differences between these 2 studies were the oxygen device in the control group and the S pO 2 goal during exercises.…”
Section: Copdmentioning
confidence: 91%
See 1 more Smart Citation
“…The authors reported that there were no improvements in endurance time or symptoms, such as dyspnea and leg discomfort, with HFNC utilization. 9 They did note, however, that transcutaneously measured partial pressure of carbon dioxide and heart rate during exercises were lower in the HFNC group than in the group receiving O 2 therapy. 9 The main differences between these 2 studies were the oxygen device in the control group and the S pO 2 goal during exercises.…”
Section: Copdmentioning
confidence: 91%
“…9 They did note, however, that transcutaneously measured partial pressure of carbon dioxide and heart rate during exercises were lower in the HFNC group than in the group receiving O 2 therapy. 9 The main differences between these 2 studies were the oxygen device in the control group and the S pO 2 goal during exercises. In the study by Cirio et al, 54 an air-entrainment mask was utilized with the same F IO 2 as HFNC.…”
Section: Copdmentioning
confidence: 91%
“…Using a randomized cross‐over trial design, these investigators found that the use of NIMV in these COPD patients with stable hypercapnic respiratory failure led to a 39% increase in endurance time on a cycle ergometer than oxygen therapy alone with lower arterial PaCO 2 and better oxygenation. On the other hand, as noted by Prieur et al ., nasal high‐flow therapy (at 60 L/min) did not improve exercise endurance during a high‐intensity exercise test, although it had a slight salutary effect on arterial PCO 2 . Thus, NIMV but not nasal high‐flow therapy can be recommended for patients with persistent hypercapnia during pulmonary rehabilitation.…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 94%
“…On the other hand, as noted by Prieur et al, nasal high-flow therapy (at 60 L/min) did not improve exercise endurance during a high-intensity exercise test, although it had a slight salutary effect on arterial PCO 2 . 18 Thus, NIMV but not nasal high-flow therapy can be recommended for patients with persistent hypercapnia during pulmonary rehabilitation.…”
Section: Novel Approaches To Hypercapnic Respiratory Failurementioning
confidence: 99%
“…The recent study of Prieur et al . explored the acute effects of NHF in 19 subjects with advanced COPD on exertional capacity within 7 days of a hospital exacerbation in a crossover design . They demonstrated no effect on symptoms of dyspnoea or exercise capacity in this context.…”
mentioning
confidence: 99%